Effect of synthesis route on the photoluminescence properties of SrTiO3:Pr,Al phosphor: Nanoparticles and microcubes - Antonio Andriotti Júnior, Mauro [UNESP]; Inês Basso Bernardi, Maria; Mesquita, Alexandre [UNESP] (Elsevier, 2023)
Sr0.998Pr0.002Ti0.998Al0.002O3 phosphors were prepared by hydrothermal (HT) and polymeric precursor (PP) methods. PP sample exhibits broadening of X-ray diffraction peaks due to the higher surface region of nanoparticles compared to HT sample. X-ray absorption spectroscopy results depicted defects associated with the formation of TiO5 octahedra for HT sample, which is ascribed to the rapid crystallization process in HT synthesis of the mesocrystals with cube-like shape. A quenching of 4f → 4f emissions in Pr3+ ions and a broad spectrum are observed for HT sample, which are attributed to structural disorder in the forming and modifying lattice due to charge compensation between Sr-O11 and Sr-O12 (or TiO5 and TiO6) clusters and intermediate levels in band gap states.